Epidemiological profile of pregnant women with syphilis in the Rio de Janeiro (Research, Society and Development, 2020)
Objective: To describe the epidemiological profile to pregnant women diagnosed with syphilis in Rio de Janeiro city (2009-2018). Methodology: epidemiological, descriptive and retrospective cross-sectional study, carried out on the online platform of Ministry of Health, Department of Informatics of Unified Health System. The data referring to maternal syphilis in the city of Rio de Janeiro come from the historical series 2009-2018 and the variables were analyzed: age group, race and education. To organize de data, Microsoft Excel was used. Results: There was the constant increase in the records of maternal syphilis, which attributes not only multiplication of the numbers of the cases, but also the increase in the records of epidemiological surveillance. It was evidenced that brown women with low level of education are more susceptible to contamination by Treponema pallidum. Conclusion: The detection rate has been progressively increasing every year, making necessary to adopt health education measures and adequate guarantee of assistance regarding the testing and treatment of syphilis, aiming at reducing notifiable cases and consequently contamination of pregnant women and vertical transmition.